(d, 3n) Reaction cross-section calculation of some reactor materials. (December 2022) - Kavun, Y.
Abstract: Nuclear reactions with charged particles have applications in many fields such as radioisotope production, industrial applications, astrophysics, etc. Therefore, examining the excitation functions performed and obtained by the activation technique is also important for understanding the nature of nuclear reactions. Also, it is especially necessary to study these reactions to estimate the effects of radiation damage on the fusion structural materials used in the construction of the first walls and core of the reactor. In this study, cross-section data have been calculated theoretically to 45 Sc (d, 3n) 44 Ti, 63 Cu (d, 3n) 62 Zn, 89 Y (d, 3n) 88 Zr, and 100 Mo (d, 3n) 99 Tc reactions in the range of 1–50 MeV energy via ALICE/ASH, TALYS 1.95 and Empire 3.2.2 nuclear reaction codes. Optical Model Parameters (OMP) calculation for deuteron-induced reaction results has been performed via TALYS 1.95 code and the calculated cross-section values are reproduced well. Also, empirically developed (d, 3n) cross section formula (Kavun, 2020) calculations have been performed at 20 MeV energy. Finally, experimental EXFOR data was compared with all results and were found to be compatible with each other. Highlights: The cross-section data have been calculated to 45 Sc (d, 3n) 44 Ti, 63 Cu (d, 3n) 62 Zn, 89 Y (d, 3n) 88 Zr, and 100 Mo (d, 3n) 99 Tc reactions. These reactions have been performed by Talys 1.95 and Empire 3.2.2 codes. Also, empirically developed (d, 3n) cross section formula (Kavun, 2020) calculations have been performed at 20 MeV energy. Finally, experimental EXFOR data was compared with all calculated theoretical results and were found to be compatible with each other.